PENERAPAN PEMBELAJARAN BERBASIS MASALAH PADA MATERI PERSAMAAN GARIS LURUS DI MTS - Murwanti, Tri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research was to find out whether the application of Problem based learning was effective in teaching a straight line equation materials to the eight grade students of MTs Negeri 1 Pontianak. This research is classified as a pre-experimental and conducted in form of one case study or post-test only design. The population of this research were 248 students of eight grade, and the samples were 42 students. Purposive sampling was used to choose the sample. The result of the data analysis showed that the study result was not reached, learning activity was quite active and student gave a positive respons, the syntax of learning was done in very good category. Based on the research findings, it can be concluded that the application of Problem based learning was not effective in teaching a straight line equation materialsÂ to the grade VIII D students of MTs Negeri 1 Pontianak because the study result was not reached and learning activity was quite active. Keywords: Effectiveness, Problem Based Learning